«АТОМ ЭЛЕКТР СТАНЦИЯСЫ ӨЗБЕКСТАНДА» ТЕМАСЫН 11-КЛАССТА ОҚЫТЫЎДЫҢ МЕТОДИКАСЫН ЖАРАТЫЎ - Жумамуратов, А.; Худайбергенова, С.; Калилаев, Ф. (FAN va JAMIYAT, 2019)
The article is devoted to the description of methods in teaching the topic “The atomic electrical power station in Uzbekistan” for the 11 grade learners of general educational schools. In contains the valuble material for training future specialists of atomic electrical power-stations.